2019
DOI: 10.1021/acs.estlett.9b00376
|View full text |Cite
|
Sign up to set email alerts
|

Emission Control of Desktop 3D Printing: The Effects of a Filter Cover and an Air Purifier

Abstract: Three-dimensional (3D) printers using the fused filament fabrication technique are in widespread use, and they are known to emit ultrafine particles (UFPs) and volatile organic compounds (VOCs). This fact raises concerns due to their impact on indoor air quality and human health. Several emission control measures have been previously proposed but without being confirmed in the near real-life situation. In this study, the effectiveness of the control measures in reducing the UFPs and VOCs was tested in a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The efficiency using only the enclosure method was 74%, but it increased to 99.95% when the emission source was enclosed with a HEPA filter. In another study, the efficiencies of a combined filter cover and air purifier to reduce ultrafine particle emissions were also determined 42 . The combined filter cover and air purifier had removal efficiencies of 74% ‐ 93%, and the filter cover at the source location was more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency using only the enclosure method was 74%, but it increased to 99.95% when the emission source was enclosed with a HEPA filter. In another study, the efficiencies of a combined filter cover and air purifier to reduce ultrafine particle emissions were also determined 42 . The combined filter cover and air purifier had removal efficiencies of 74% ‐ 93%, and the filter cover at the source location was more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al [94] used a desktop 3D printer with ABS filament material within a standardized 30 m 3 environmental test chamber to study the effectiveness of control measures such as a filter cover and an air purifier with different filters in reducing exposure to UFP and VOCs. The filter cover was reported to provide the highest reduction in UFP exposure (93%), compared to lower reduction provided by the air filters (89-74%).…”
Section: Assessment and Characterisation Of The Emissionsmentioning
confidence: 99%
“…This finding suggests that implementing control measures at the source location is more efficient than trying to remove particles after emission. Reducing VOCs was found to be a significantly more complex task, as it was observed that the use of the control devices results in the emission of several new VOCs [94].…”
Section: Assessment and Characterisation Of The Emissionsmentioning
confidence: 99%
See 2 more Smart Citations